Analisis Visual Mahkota Binokasih Sang Hiyang Pake di Kabupaten Sumedang - Jeng Oetari; Fajar Ciptandi; Morinta Rosandini (JURNAL RUPA, 2023)
Regency, especially the Sumedang Larang Palace, was designated as the Sumedang Puseur Budaa Sunda in 2017 by the Sumedang Government and designated as an institution for the preservation, protection, and development of ancestral customs and culture. As a result of this policy, 10 typical Kesumedan ornaments were determined, one of which was the Binokasih Crown. On the other hand, the Regent's Regulation Number 113 of 2009 concerns legal developments and community needs, therefore to strengthen legality it is necessary to increase it in the form of regional regulations, to maintain cultural preservation which is carried out through inventory, security, maintenance, rescue, and publication. So that is more potential in digging up further information, one of which is in the visual analysis of objects related to culture, especially the ornaments on the Crown which have been designated as cultural heritage/cultural assets for efforts to preserve Sundanese culture in Sumedang. The purpose of this study is to visually analyze the crown and analyze the philosophy contained in the crown. So that it can maintain cultural heritage both tangible and intangible aspects and become a basic reference in developing a product because it already has a clear foundation. Keywords: Visual Analysis, Crown Binokasih, Decorative Variety, Sumedang